Human-machine reconfigurations plans and situated actions - Suchman, Lucy 1951- (Learning in doing : social, cognitive and computational perspectives, 2007)
This 2007 book considers how agencies are currently figured at the human-machine interface, and how they might be imaginatively and materially reconfigured. Contrary to the apparent enlivening of objects promised by the sciences of the artificial, the author proposes that the rhetorics and practices of those sciences work to obscure the performative nature of both persons and things. The question then shifts from debates over the status of human-like machines, to that of how humans and machines are enacted as similar or different in practice, and with what theoretical, practical and political consequences. Drawing on scholarship across the social sciences, humanities and computing, the author argues for research aimed at tracing the differences within specific sociomaterial arrangements without resorting to essentialist divides. This requires expanding our unit of analysis, while recognizing the inevitable cuts or boundaries through which technological systems are constituted